SWOT Analysis as an Innovation Strategy in Improving PT XYZ's Business Sustainability - Bintang Afrina Putri; Hapzi Ali (Siber International Journal of Sport Education, 2025)
This study aims to create a sustainable fashion industry innovation strategy using a SWOT analysis approach to PT XYZ, a company that makes formal and casual clothing for sale domestically and abroad. The object of this study is PT XYZ, a company that makes formal and casual clothing for sale domestically and abroad. This company is facing challenges to maintain the sustainability of its business amidst increasingly dynamic competition in this industry. The research method uses a qualitative descriptive approach based on literature studies. SWOT analysis is an analysis of strengths, weaknesses, opportunities, and threats that can affect the sustainability of a company. The results of the analysis show that PT XYZ has advantages in innovative product design and flexible production systems, but has weaknesses in terms of branding and digital distribution worldwide. While opportunities come from environmentally friendly fashion trends and market digitalization, threats come from shifting trends, global fast fashion, and supply chain uncertainty. The strategies made include increasing digital branding, investing in environmentally friendly materials, collaborating with local designers, and improving supply chain management.